[PP.15.01] ESTIMATION OF 24-H URINE SODIUM FROM SPOT URINE: A TENDENCY OF MOVING ESTIMATED MEAN TOWARD TO MEAN OF POPULATION FROM WHICH REGRESSION MODEL WAS ESTABLISHED. (September 2017) - Rhee, M.; Kim, J.H.; Shin, S.J.; Nah, D.Y.; Park, J.H.; Kim, S.W.; Gu, N.; Park, D.G.
Abstract : Objective: Most equations estimating 24-h urine sodium (e24HUNa) from single spot urine have developed by using regression model of sample population. Those equations have been challenged its tendency of under- and over estimation of e24HUNa depending on the amount of sodium intake. We hypothesized that the mean of e24HUNa from single spot urine depends on the mean of measured 24-h urine sodium (m 2 4HUNa) of population from which regression model was established. Design and method: A population (n = 791) was divided into (1) septiles and (2) quintiles with the level of m 2 4HUNa. In each septile, e24HUNa was calculated by using previously suggested equations (Kawasaki, Tanaka, and Danish equations), and compared to m 2 4HUNa. In each quintile, e24HUNa was calculated by estimating equations developed from remainders of population by using regression model, and compared to m 2 4HUNa. Results: Mean e24HUNa calculated by tested equations was higher than m 2 4HUNa in septiles with lower m 2 4HUNa compared to mean m 2 4HUNa of development population from which regression equation was developed, but lower in septiles with higher m 2 4HUNa, showing a tendency of moving e24HUNa toward to the mean of development population, from which regression equations were developed. Regression equations, developed from population excluding each quartile, showed overestimation in quartiles of low m 2 4HUNa and overestimation in quartiles of high m 2 4HUNa. Conclusions: Estimation of mean sodium intake at population level from single spot urine by using regression equations showed a tendency of moving the calculated mean toward to the mean of population, from which regression model was established. This phenomenon suggests that estimation of sodium intake at the population by using single spot urine should be reappraised.